Preparation and in vitro characterization of poly (epsilon-caprolactone)-based tamoxifen citrate- loaded cylindrical subdermal implant for breast cancer - Hiremath, Jagadeesh G; Devi, V Kusum (Asian Journal of Pharmaceutics (AJP), 2014)
In the present study cylindrical poly(epsilon-caprolactone) (PCL)-based biodegradable polymeric tamoxifen citrate-loaded subdermal implants were prepared by laboratory-based modified melt extrusion technique. The prepared implants were evaluated for their physicochemical parameters. Drug content in implants by high-performance liquid chromatographic (HPLC) method, differential scanning calorimetry (DSC), X-ray diffraction (XRD) and scanning electron microscope (SEM) studies of tamoxifen citrate-loaded implants. Determination of in vitro hydrolytic degradation of polymeric and tamoxifen citrate-loaded implants and in vitro drug release was carried out by using indigenously developed dissolution apparatus. DSC and XRD studies proved that the drug is entrapped in the implant. The highest rate of hydrolytic degradation (weight loss) was observed in blank implants when compared to tamoxifen citrate-loaded implants.The studies proved that the developed method have potential in terms of industrial feasibility.